METODE PDAT DAN COMSTOCK LEBIH EFISIEN DIBANDINGKAN FOOD WEIGHING DALAM MENILAI SISA MAKANAN PASIEN - Nisak, Nova Khairun; Ronitawati, Putri; Palupi, Khairizka Citra (Lembaga Penerbitan Unversitas Esa Unggul, 2019)
Food waste is one of indicator to measure the quality of food service system. The most frequent method in assessing food waste is the Comstock visual method. Recently, PDAT (Pictorial Dietary Assessment Tool) has been identified as another valid and reliable method in assessing food waste. However, it remain unknown the difference of quantity and times between Comstock, PDAT and food weighing (gold standard) method. The aim of this study is to identify the difference of quantity and times of assessment between Comstock, PDAT and food weighing methods. This was quasi experimental study which assesses food waste by using three methods (Comstock, PDAT and food weighing) in Koja Hospital, North Jakarta. Comstock and PDAT methods were done by nutritionist at Koja Hospital and food weighing conducted by researchers. Total sample of this study was 70 trays. We found that there was no significant difference on quantity of food waste between methods of PDAT versus Comstock, PDAT versus food weighing, and Comstock versus food weighing (p>0.05). The time of assessment demonstrated significant difference between methods of PDAT versus food weighing and Comstock versus food weighing (p<0.05). However, there was no significance different in time of assessment between method of PDAT and Comstock. In conclusion, The PDAT, Comstock and Food weighing methods produce similar results in assessing the quantity of patient food waste. PDAT and Comstock methods were more efficient than food weighing in assessing the patient's food waste Keywords: food waste, PDAT, Comstock, Food weighing